Implications in adjusting a gravity network with observations medium or independent: analysis of precision and reliability - Pedro L. Faggion; Camil Gemael; Sílvio R. C. de Freitas; Guataçara dos S. Junior (Revista Brasileira de Cartografia, 2005)
Adjustment strategies associated to the methodology applied used to the implantation of a gravity network of high precision in Paraná are presented. A network was implanted with stations in 21 places in the State of Paraná and one in the state of São Paulo To reduce the risk of the losing of points of that gravity network, they were established on the points of the GPS High Precision Network of Paraná, which possess a relatively homogeneous geographical distribution. For each one of the gravity lines belonging to the loops implanted for the network, it was possible to obtain three or six observations. In the first strategy, of adjustment investigated, for the net, it was considered, as observation, the medium value of the observations obtained for each gravity line. In the second strategy, of the adjustment, the observations were considered independent. The comparison of those strategies revealed that only the precision criteria is not enough to indicate the great solution of a gravity network. It was verified that there is need to use an additional criterion for analysis of the adjusted solution of the network, besides the precision criteria. The reliability criterion for geodesic networks, which becomes separated in reliability internal and external reliability it was used. The reliability internal it was used to verify the rigidity with which the network reacts in the detection and quantification of existent gross errors in the observations, and the reliability external in the quantification of the influence on the adjusted parameters of the errors non located. They are presented the aspects that differentiate the obtained solutions, when they combine the precision criteria and reliability criteria in the analysis of the quality of a gravity network.